Evaluation of Epley’s manoeuvre efficacy in posterior semicircular canal benign paroxysmal positional vertigo - Singh, Divyanshi; Thakur, Abhishek Singh; Guleria, Trilok Chand; Sharma, Disha; Mahajan, Manisha (International Journal of Research in Medical Sciences, 2023)
Background: Benign paroxysmal positional vertigo (BPPV) is the most prevalent cause of peripheral vertigo in the outpatient department. Methods: After applying inclusion and exclusion criteria, 53 patients out of 96 who visited the outpatient department were included in this study. To rule out other disorders, pure tone audiometry, computed tomography etc were performed if needed. Epley's manoeuvre was performed, and the patient's response was noted. The manoeuvre was performed during weekly appointments, and the number of visits necessary by each patient was recorded. The patients were followed up for four months. Results: Mean age of the patients was 48 years. In this study, out of 53, there were 31 females (58.49%) and 22 males (41.50%). The female to male ratio was 1.4:1. All patients experienced positional vertigo, which was accompanied by nausea and vomiting. The right side was found to be more involved in our study than the left. Out of 53 patients, 23 patients (43.39 %) recovered in the first visit, 15 patients (28.30 %) recovered in second visit, 8 patients (15.09 %) recovered in the third visit and remaining 7 patients (13.20 %) recovered in fourth visit. All the patients recovered eventually. In 5 out of 53 cases, that is, in 9.43%, recurrence was seen with return of the BPPV symptoms. Conclusions: We concluded that majority of patients for whom Epley’s manoeuvre was done recovered after the first visit itself. Patients presenting with recurrence were less probably due to the shorter period of follow up.